The journey of research data: Accessing nordic health data for the purposes of developing an algorithm. (March 2022) - Cathaoir, Katharina Ó; Gunnarsdóttir, Hrefna Dögg; Hartlev, Mette
This article traces the journey of Nordic health data requested for developing a healthcare algorithm. We focus on the legal requirements and highlight that differences in the legislation of Denmark, Norway and Iceland, and the interpretation thereof by responsible bodies, can pose a barrier for scientific researchers. In addition, non-legal institutional requirements or practices may hamper data access. First, despite some European harmonization, the mandate of research ethics committees and the data protection authorities vary in the three countries. Second, domestic institutions impose tailored requirements, sometimes only allowing domestic or affiliated researchers to access data sets. Third, the manner in which a dataset is collected, catalogued and stored has implications for data access. We make several recommendations for increasing transparency in Nordic data access, such as, increasing knowledge sharing regarding interpretation of General Data Protection Regulation (GDPR) criteria, adopting clearer regulations and pursuing greater citizen engagement in secondary use of health data.